The escape backwards as an escape forwards. Moments of demythification in Christa Wolfs Cassandra and Medea (Myth and Subversion in Contemporary Novel, 2012)
The aim of this study is to discuss demythification and the subversion of myth in Christa Wolf’s Cassandra Project (1983) and Medea. Stimmen (1996). Wolf considers literature as an archaeological project, as a quest for the truth and the “blind spots” in personal and social history. On this quest she turns her attention to Greek mythology. A myth is not a context, but a frame. It is a supertemporal, multidimensional phenomenon, which allows a writer to move into free spaces. Thus, Wolf’s versions revise the myth in some fundamental points. Her main concern is to shed light on the manipulation of truth and the discrimination of the stranger. The author does not write, however, against the myth per se. On the one hand she points out the close connection between myth and politics and on the other hand she tries to explore the potential of myths in order to understand the present situation better and to look for livable alternatives or yet untried patterns. The reminiscence on the origins of the alienation offers a matrix for the explanation of today’s conditions and at the same time permits a glimpse into the future: “the escape backwards as an escape forwards”.